Pengaruh Belanja Daerah dan Investasi Terhadap Kesejahteraan Masyarakat Melalui Pertumbuhan Ekonomi Pada Kabupaten/Kota Provinsi Bali - Krismajaya, Putu; Martini Dewi, Ni Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 6, Juni 2019, pp (1181-1442), 2019)
ABSTRACT This study aims to determine the direct effect of Regional Expenditures and Investment on Economic Growth in the Regency / City of Bali Province, as well as the indirect influence of Regional Expenditures and Investment on Community Welfare through Economic Growth. This research covers 9 regencies / cities in the province of Bali. In the last five years the rate of Regency / City Economic Growth in the Province of Bali has increased. In addition to the increasing growth rate, the pace of employment in Bali Province has also increased from year to year. But the phenomenon that occurs is still the gap of economic growth between regencies / cities in Bali Province. The analysis technique used is path analysis. The results showed that Regional Expenditures had a positive and significant direct effect on economic growth in Bali Province. Regional expenditure does not have a direct positive and significant effect on the welfare of the people in the Bali Province. Regional expenditure has a significant effect on people's welfare through Economic Growth in the Province of Bali. Keywords: regional expenditure, investment, community welfare, economic growth.